“Blessed to be a Blessing” RINGKASAN KHOTBAH - Yoges Mahendra Saragih (MAWAR SARON: Jurnal Pendidikan Kristen dan Gereja, 2021)
irst, we are people who are blessed by God. Maybe we think that at times like this, it is difficult for us to feel God's blessings in our lives. However, do we realize that the Lord Jesus never stops blessing us? If you can come to church today with a healthy body, that is God's blessing. If today you can still have breakfast in the morning, it is God's blessing. If today we can still live, it is God's blessing. Second, God blesses us with a purpose. God never does anything without a lofty purpose. Peter said that let us serve according to the gifts that God has given us. Dear friends, this is what we as Christians to do in difficult times like these. We must be a blessing to others.